Incidencia de los recursos didácticos interactivos dentro del proceso de enseñanza aprendizaje en el área de matemática en la Escuela Luis Felipe Borja, de la parroquia Toacaso, cantón Latacunga en el año lectivo 2014 - 2015 - Marcalla Casa, Gloria Marina (2015)
This research was done to investigate the incidence that the interactive teaching resources have into the teaching-learning process in mathematics area at Luis Felipe Borja School in Toacaso Parish, Latacunga canton. This investigation has taken into account the independent variable which is the interactive teaching resource and the dependent variable which is the teaching-learning process. It allowed to analize the teaching-learning process which teachers lead every day in the classroom as well as the academic performance showed by the students of the institution through the traditional teacher`s method. It was used a field research which the technique of the interview and the survey were used and the questionnaire as instrument. They were applied to the principal, teachers and students respectively. The information was tabulated and displayed in tables and graphs. With the results of the investigation, it was stated conclusions and recommendations. The investigation is a contribution to solve the problems which were detected in the education field and give a quick solution, using new options such as the use of ICT to enhance the teaching of Mathematics. For the proposal, it has been considered to carry out eight training workshops to the staff of the institution about the use of the virtual classroom. It has promoted the improvement of Mathematics teaching, thus, It was gotten an initiative that is feasible and favorable for the educational community, especially to teachers with the purpose to use the technology resources permanently in the labor and social area. This has allowed at the same time to change the traditional methodology and improve the education system.